2004
DOI: 10.2527/2004.82103038x
|View full text |Cite
|
Sign up to set email alerts
|

Growing and finishing performance of steers when fed recycled poultry bedding during the growing period1

Abstract: Sixty Angus-cross steers were used to compare the effects of recycled poultry bedding (RPB) stacking method and the inclusion of monensin in growing diets on performance. Steers were individually fed balanced, growing diets for a period of 84 d. The diets were control (CON), CON + monensin (CON+M), deep-stacked RPB (DS), DS+M, shallow-stacked RPB (SS), and SS+M. The CON diets contained corn, soybean meal, corn silage, and cottonseed hulls. In the RPB diets, 35% of the silage, cottonseed hulls, and soybean meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…The RPB used in our study had an NDF and ADF content close to the amounts reported by Azizi-Shotorkhoft et al (2012; 353 and 185 g/kg of DM, respectively) and Obeidat et al (2011;334 and 215 g/kg of DM, respectively), whereas the respective values in the current study were less than the amounts reported in the study of Capucille et al (2004;528 and 317 g/kg of DM, respectively). It seems that the NDF content of the RPB can vary substantially due to various factors such as the type of bedding material used (e.g., straw, wood shavings, rice hulls, corn cobs, and peanut hulls) and the extent of heat damage occurring during heat processing (Capucille et al, 2004), indicating the importance of determining the chemical composition of RPB before incorporating it into diets. Due to high negative correlation reported between ash and ME content of the RPB, the ash content is one of the most important measures of the quality of RPB (R 2 = -0.97; Deshck et al, 1998).…”
Section: Chemical Composition and Biological Analysis Of Recycled Pousupporting
confidence: 81%
See 1 more Smart Citation
“…The RPB used in our study had an NDF and ADF content close to the amounts reported by Azizi-Shotorkhoft et al (2012; 353 and 185 g/kg of DM, respectively) and Obeidat et al (2011;334 and 215 g/kg of DM, respectively), whereas the respective values in the current study were less than the amounts reported in the study of Capucille et al (2004;528 and 317 g/kg of DM, respectively). It seems that the NDF content of the RPB can vary substantially due to various factors such as the type of bedding material used (e.g., straw, wood shavings, rice hulls, corn cobs, and peanut hulls) and the extent of heat damage occurring during heat processing (Capucille et al, 2004), indicating the importance of determining the chemical composition of RPB before incorporating it into diets. Due to high negative correlation reported between ash and ME content of the RPB, the ash content is one of the most important measures of the quality of RPB (R 2 = -0.97; Deshck et al, 1998).…”
Section: Chemical Composition and Biological Analysis Of Recycled Pousupporting
confidence: 81%
“…Using RPB in a ruminant diet has always been controversial and has stimulated a great deal of study in defense of its safety (Capucille et al, 2004;Obeidat et al, 2011). The presence of pathogenic organisms in raw RPB (Jeffrey et al, 1998;Martin et al, 1998) and heavy metals, which might cause serious hazards to animal and human health, are cause for safety concern (Rankins et al, 2002).…”
Section: Chemical Composition and Biological Analysis Of Recycled Poumentioning
confidence: 99%
“…Deep stacking or ensiling poultry litter is commonly recommended as a pretreatment to improve its safety and palatability as a feed for ruminants (Capucille et al, 2004;Bush et al, 2007). Bush et al (2007) showed that despite the wide variation of temperature within the stacks, Salmonella was eliminated in 98.7% of all inoculated sites.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Agriculture (USDA) 2005a]. Data from animal-production researchers demonstrate that the quality of these products is directly related to animal feeding practices (Capucille et al 2004; Gatlin et al 2003; Zaghini et al 2005). Therefore, given the high consumption of animal-based food products in the United States, the ingredients used in animal feed are fundamentally important in terms of both the quality of the resulting food products and the potential human health impacts associated with the animal-based food-production chain.…”
mentioning
confidence: 99%